GASTRIC BEZOAR AND SUBSEQUENT BLEEDING IN A 73-YEAR OLD WOMAN – CASE REPORT - Michał Szalach; Mateusz Jasiński; Zuzanna Rabczak; Marcin Narloch; Kamila Mozga; Małgorzata Kuczek; Jakub Rusek; Justyna Tasior; Bartosz Burda; Justyna Wyroślak-Najs (International Journal of Innovative Technologies in Social Science, 2025)
Bezoar is a mass of swallowed foreign material most often composed of hair or fiber. Commonly, bezoars occur in young women with a history of psychiatric disorders, especially trichotillomania and trichophagia. Diagnostically, gastroscopy remains the gold standard. Prevalence is low, affecting up to 0.4% of the general population. Bezoars can lead to ulcer formation and hemorrhagic complications. Literature describes various treatment options, including endoscopic, laparoscopic and open surgical approaches. Psychiatric consultation and follow up are crucial for recurrence prevention. A 73-year old woman with a history of gastric ulcers and depression was urgently admitted to general surgery ward due to fatigue, abdominal pain and a suspicion of gastrointestinal hemorrhage. Outpatient gastroscopy revealed extensive ulceration of the posterior wall of the stomach, a large bezoar and pyloric stenosis. On admission, patient was severely anemic. Endoscopic haemostasis proved unfeasible due to the large bezoar. After initial stabilization, operative treatment was recommended. Laparotomy was performed revealing thickening on the posterior wall of the stomach, stenosis of the duodenum and a large diverticulum on the anterior wall of the descending part of the duodenum. Subtotal gastrectomy and diverticulum resection was performed. Restoration of gastrointestinal continuity was carried out using the Roux-en-Y method. Examination of the specimen confirmed the presence of a four centimeter bezoar and a three centimeter gastric ulcer. Post-surgery period was complicated by pneumonia and peripheral pulmonary embolism. Patient was discharged after treatment in good general and local condition after fifteen days since admission. Despite being rare, bezoars occur and should be taken into consideration during differential diagnosis of gastric symptoms and dyspepsia, even in the elderly population, especially with a history of psychiatric disorders. Bezoars can prevent endoscopic treatment of gastric hemorrhage and force surgeons to perform extensive surgical resections.